The Role of Social Assistance for the Family Hope Program (PKH) in Tackling Stunting in Dewantara District, North Aceh Regency - Alba, Amru; Farida, Ratna; Abdullah, Amiruddin (Al-Fikrah, 2024)
This study aims to examine the role of the Family Hope Program (PKH) social assistants in tackling stunting in Dewantara District, North Aceh Regency, using role theory that includes participation, perception, accessibility, and action determination in tackling stunting. This research was conducted in Dewantara District, North Aceh Regency. The method used is qualitative, with data collection techniques including interviews, observations, and documentation. Data analysis was carried out by selecting, simplifying, classifying, presenting, and drawing conclusions. The results of this study indicate that the Family Hope Program social assistants have actively participated, have good perceptions, and have taken positive actions in tackling stunting in Dewantara District, North Aceh Regency through Family Capability Improvement Meetings (P2K2), although the accessibility in tackling stunting is not yet optimal. Barriers encountered in tackling stunting include the lack of understanding among PKH beneficiaries about stunting, reluctance to fully follow government programs for stunting prevention, poor environmental hygiene, and a lack of awareness among men to refrain from smoking near infants and pregnant women.